A interação do usuário com catálogos bibliográficos on-line: investigação a partir da Teoria Fundamentada - Bastos, Flávia Maria [UNESP] (2013)
This research aims to identify ways of user interaction with the Online PublicAccess Catalog, through a process of information search in order to find bibliographic resources. For the development of this research the chosen methodology was the Grounded Theory in order to identify patterns as well as the conditions under which the data apply in that context. For this, the collected and analyzed data cover the period 2008-2012, which allow identification of core categories of users through various refinements of the achieveddata with a constant comparative analysis to reach data saturation. Thus, the data were gatheredinto dimensions of search, staff, databases, knowledge areas, and time (year, month and a half) that identify manypossible forms of interaction patterns in the central categories of users with the onlinebibliographic catalog options. Results are presented bygeneral characteristics of the highlighted data and also by the central categories of user patterns. Thus , the data demonstrate the profile and user preference for a quick interaction with the systemthat is characterized by anonymity, due to mostusers do not identify themselves when conducting their research using the default search option to the system, mostly. Thus, based on the patterns of interaction, we present a model of user interaction with the online library catalog of UNESP, which shows the current user behavior that must be assimilatedby the managers of bibliographic catalogs during their future actions, to guide Librarianship practiceswith focus on the user.